The Evaluation of Nurses’ Knowledge and Practice About the Temperature of Milk Fed to Infants: A Descriptive Study - (:unkn) unknown (My University, 2019)
Aim: The study aimed to evaluate the practices and knowledge of nursesin the neonatal intensive care unit regarding temperature of breastmilk/formula given to infants during feeding.Methods: This descriptive study comprised 116 neonatal nurses workingin an intensive care unit. The research data were collected using the NurseIdentification Questionnaire and the Practices and Knowledge of NursesRegarding Milk Temperature Questionnaire.Results: Of the nurses, 52.6% stated that the milk given to infants shouldbe beneath 35°C, 47.4% stated that it should be above 35°C, and 76.4%stated that the temperature of the breastmilk/formula given to infantsmay cause nutrient loss. It was found that 78.4% of the nurses heatedthe milk in a warming bath, 6% heated the milk by keeping it at roomtemperature, and 15.6% preheated the milk with a heater and thermostat.Furthermore, 91.4% of the nurses were found to test the temperatureof the breastmilk/formula by placing some on the inner segment of theforearm, 5.2% by using a liquid thermometer, and 3.6% by placing someon the palm.Conclusion: It was determined that the nurses had insufficientknowledge regarding the proper temperature of the breastmilk/formulaand used traditional methods for heating milk and testing its temperature.

Amaç: Yenidoğan yoğun bakım ünitesinde çalışan hemşirelerin bebeklere verdikleri süt ısısına ilişkin uygulama ve bilgilerini değerlendirmektir. Yöntem: Araştırma 116 yenidoğan yoğun bakım hemşiresi ile yapılmıştır. Veriler Hemşireyi Tanıtıcı Bilgi Formu ve Hemşirelerin Süt Isısına İlişkin Uygulama ve Bilgileri Anketi ile toplanmıştır. Bulgular: Katılımcıların %52.6’sının bebeklere verilen anne sütü/formül süt ısısının 35°C’nin altı, %47.4’ü 35°C’nin üstü olması gerektiğini ve %76.4’ü bebeklere verilen sütün ısıtıldığı sıcaklığın besin kayıplarına neden olduğunu belirtmiştir. Katılımcıların %78.4’ünün anne sütü/ formül sütü sıcak su dolu kapta bekleterek, %6’sının oda sıcaklığında bekleterek, %15.6’sının termostatlı ısıtıcı ile ısıttığı saptanmıştır. Aynı zamanda katılımcıların %91.4’ünün anne sütü/formül sütün ısısını bebeğe vermeden önce ön kolun iç yüzü ile, %5.2’sinin sıvı termometresi ile %3.6’sının el/avuçiçi ile değerlendirdikleri bulunmuştur. Sonuç: Araştırma sonucunda hemşirelerin bebeklere verilmesi gereken süt ısısı ile ilgili yeterli bilgiye sahip olmadıkları görülmüştür. Hemşirelerin süt ısıtırken ve sıcaklığını değerlendirirken geleneksel yöntemleri tercih etikleri saptanmıştır.
Bebeklere Verilen Süt Isısına Yönelik Hemşirelerin Bilgi ve Uygulamalarının Değerlendirilmesi: Tanımlayıcı Bir Çalışma
Keywords: Hemşirelik